Analysis of the Leadership Style of the Mayor of Bandung 2025 Through the Vision and Mission Approach - Sheravina Maulidya; Alvin Al-Amin; Dandi Ramdani; Rizal Gunawan; Muhammad Yaris Khalifah; Susanah Susilawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study explores the leadership model of Muhammad Farhan, the 2025 Mayor of Bandung, by examining how his leadership aligns with the city's vision and mission. Utilizing a descriptive qualitative method, data were sourced from official government platforms, reputable online news, and audiovisual materials reviewing his first 100 days in office. The analysis reveals that Farhan employs a combination of transformational, bureaucratic-adaptive, and participatory leadership styles. His focus lies in promoting innovation, enhancing digital public services, and encouraging community engagement in decision-making. Nevertheless, challenges persist, such as a relatively low initial public satisfaction rate (44%) and criticism of his preference for ceremonial activities over addressing fundamental urban issues such as waste management and traffic congestion. The study suggests improving two-way communication with the public, increasing leadership presence in the field, and fostering active public involvement in the evaluation of government programs.